Bladder Neoplasia in Pediatric Patients-A Single-Center Experience Including a Case Series - Frank-Martin Haecker; Elisabeth Bruder (MDPI AG, 2023)
Objective: Bladder lesions like urothelial carcinoma are rare in the first two decades of life. A biopsy of the bladder or urinary cytological examination is seldom required. Gross painless hematuria is the most relevant clinical syndrome. Methods: A retrospective analysis of surgical pathology records collected between 1984 and 2014 at our institution was performed in a search for cases of urothelial neoplasms originating within the urinary bladder in pediatric patients. Diagnoses were confirmed based on pathologic examination using the 2004 World Health Organization (WHO) classification system. We selected keywords such as bladder neoplasia, bladder lesion, urothelial neoplasia, rhabdomyosarcoma, and children. In addition, we describe clinical presentation and diagnostic procedures as well as treatment and follow-up of two patients. A review of the literature was performed to analyze recommendations concerning diagnostic staging, treatment, and follow-up examinations as well as surveillance of urothelial tumors in the pediatric population. Results: Screening the pathology database of the Institute of Medical Genetics and Pathology of the University Hospital Basel between 1988 and 2014 yielded 287 samples involving the urinary bladder, 110 autopsies, 135 biopsies, and 42 cytology specimens. Of these, most samples originated from malformations and inflammation. Only five were tumors: two were urothelial tumors and three were rhabdomyosarcomas. The majority of specimens comprised resections of the diverticula or distal ureter. Our case reports include two patients with a urothelial tumor. Among the urothelial tumors, one was a papillary urothelial neoplasm of low malignant potential (PUNLMP). Painless hematuria was the directing clinical symptom. The tumor was investigated by FISH, and a 9p21 deletion was found. The second tumor-like lesion was a fibroepithelial polyp arising from the bladder neck. Conclusions: Bladder tumors in children are rare and mostly consist of urothelial and mesenchymal neoplasms. Rhabdomyosarcoma is the most common malignant bladder tumor in childhood. Similar to adult urothelial neoplasms, the loss of 9p21 is also implicated in urothelial neoplasms in childhood. Despite an increasing number of case reports and small series published within the last 2 decades, general treatment protocols including recommendations for staging, tumor markers, and follow-up examinations are still not yet available for this tumor entity in the pediatric population.